Dengue hemorrhagic fever: Clinical efficacy of vitamin K - Srigade, Vedavyasa (Indian Journal of Child Health, 2016)
Background: At present dengue is the most significant viral infection affecting public health and survival. Bleeding in dengue due to many reasons can cause significant anemia and death. Elevation of prothrombin time (PT) in dengue points to liver failure and consequent bleeding. Objective: Ability of vitamin K to stop bleeding in dengue hemorrhagic fever (DHF) is examined in this study. Methods: It is a retrospective review of medical records of children admitted with confirmed and clinical DHF. Children in the age group of 1 month to 15 years from June to November of 2015 at the Institute of Child Health, Niloufer Hospital, Hyderabad, were included in the study. WHO guidelines were used to define clinical and confirmed DHF cases. Cessation of bleeding within 24 h of vitamin K administration without recurrence was taken as clinical evidence of efficacy of vitamin K. Results: Of the 100 patients with confirmed DHF, 26 met the inclusion criteria, and of the 133 clinical DHF, 27 met the inclusion criteria. The presentation of bleeding in decreasing order of frequency was malena, epistaxis, hematuria, hematemesis, gum bleed, ecchymoses, and hematochezia. Deranged PT was seen in nearly 100% of the patients, and hepatomegaly was seen in 77% patients, while thrombocytopenia was seen in 80% patients. Clinical response to vitamin K was seen in 80.8% of confirmed (95% confidence interval [CI]: 60-92.7%) and 92.6% of clinical DHF (95% CI: 74.2-98.7%). Conclusions: In the study group, presentation of bleeding suggests coagulation failure as the main contributor to bleeding rather than thrombocytopenia. Overall response rate to vitamin K was 86.8% (95% CI: 74-94%). Early institution of vitamin K in DHF may prevent anemia, and reduce the need for transfusions.